Theory of quadratic estimates of variance - Petunin, Yu. I.; Tupko, N. P. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
A class of quadratic estimates is constructed for the second-order moment and variance of a random variable. These estimates are found on the basis of sample values obtained by simple sampling. The best quadratic estimates are found for the second-order moment and variance in the case of known mathematical expectation. The exactness of biased and unbiased estimates of variance is investigated in the case of unknown mathematical expectation.